2022
DOI: 10.1186/s12711-022-00768-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of colostrum refractive index and its use as a proxy for the concentration of immunoglobulins in Holstein cattle

Abstract: Background Colostral concentration of immunoglobulins (Ig) is crucial for the passive transfer of antibodies from the cow to the new-born calf. Direct determination of Ig by the gold standard radial immunodiffusion method is demanding in terms of time and costs. For this reason, a refractometer is commonly used at the farm level for an indirect estimation of colostrum quality, which is given as the Ig concentration. In this study, colostrum samples were collected from 548 Italian Holstein cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Feeding management may also lead to changes in the quality of BC, and it has been found that dairy cows vaccinated at 28 days of expected farrowing and started on an acidproducing diet 21 days before farrowing can increase the concentration of IgG in BC [75]. In addition, genetic traits also have a role in the quality of BC, but this is controversial and has had opposed results in different studies [62,[76][77][78]. Again, this reflects the complex diversity of factors influencing BC quality.…”
Section: Other Factorsmentioning
confidence: 99%
“…Feeding management may also lead to changes in the quality of BC, and it has been found that dairy cows vaccinated at 28 days of expected farrowing and started on an acidproducing diet 21 days before farrowing can increase the concentration of IgG in BC [75]. In addition, genetic traits also have a role in the quality of BC, but this is controversial and has had opposed results in different studies [62,[76][77][78]. Again, this reflects the complex diversity of factors influencing BC quality.…”
Section: Other Factorsmentioning
confidence: 99%
“…In order to reduce infection rates for both diseases, it is considered more appropriate to prioritize preventive measures in the management system along with immunization. This includes protocols such as cleanliness in the maternity ward, immediate weaning of the calf at birth, placing the calf in individual pens, placing a newly hatched calf in a clean pen, feeding the calf with a personal teat, and not handling the calves with dirty tools (Costa, 2022).…”
mentioning
confidence: 99%